Do edible oils reduce bacterial colonization of enamel in situ? - Hannig, Christian; Kirsch, Jasmin; Al-Ahmad, Ali; Kensche, Anna; Hannig, Matthias; Kümmerer, Klaus (Clinical oral investigations, 2013)
Objective Edible oils are an empiric approach for the prevention of oral diseases. The present in situ study investigated the effect of edible oils on initial bacterial colonization of enamel surfaces. Methods and materials Initial biofilm formation was performed on enamel specimens mounted on maxillary splints and carried by eight subjects. After 1 min of pellicle formation, rinses with safflower oil, olive oil and linseed oil were performed for 10 min. Application of chlorhexidine for 1 min served as positive control. Afterwards, the slabs were carried for 8 h overnight. Samples carried for 8 h without any rinse served as negative controls. The amount of adherent bacteria was determined by DAPI staining (4′,6-diamidino-2-phenylindole) and live–dead staining (BacLight). Additionally, determination of colony forming units was performed after desorption of the bacteria. TEM evaluation was carried out after application of the rinses. Results The number of adherent bacteria on control samples was 6.1 ± 8.1 × 10 5 /cm 2 after 8 h (DAPI). Fluorescence microscopic data from DAPI staining and live–dead staining as well as from the determination of CFU revealed no significant effects of rinsing with oils on the amount of adherent bacteria compared to the non-rinsed control samples. However, with chlorhexidine a significant reduction in the number of bacteria by more than 85 % was achieved (DAPI, chlorhexidine: 8.2 ± 17.1 × 10 4 /cm 2 ). The ratio of viable to dead bacteria was almost equal (1:1) irrespective of the rinse adopted as recorded with BacLight. TEM indicated accumulation of oil micelles at the pellicle's surface and modification of its ultrastructure. Conclusion Rinses with edible oils have no significant impact on the initial pattern and amount of bacterial colonization on enamel over 8 h. Clinical relevance Rinses with edible oils cannot be recommended for efficient reduction of oral biofilm formation.